Antioxidant and Antifungal Activities of Temu mangga (Curcuma mangga Val.) Extract in Some Solvents: Antioxidant and Antifungal Activities of C. mangga - Muchtaromah, Bayyinatul; Nurul Mutmainah, Fitria; Agung Prahardika, Bayu; Ahmad, Mujahidin (Iranian Journal of Pharmaceutical Sciences, 2020)
Temu mangga (Curcuma mangga Val.) has been widely used to overcome health problems in Indonesia, one of them used as the ingredient of Madurese herbal medicine. The active compounds contained in C. mangga extract have potential as a medicine to improve female fertility. This study aims to determine the content of phytochemicals, antifungal, and antioxidant activity of C. mangga rhizome extract in some solvents based on their polarity. C. mangga rhizome was extracted by a maceration method using ethanol (polar), chloroform (semi-polar), and n-hexane (non-polar) solvents. Standard phytochemical methods were used for preliminary phytochemical screening of the plant extracts. Antioxidant activity was tested using the DPPH method with extract concentrations of 25, 50, 100, 200, and 400 ppm. The antifungal activity test against Candida albicans used the Kirby Bauer method with a 100% concentration and microdilution method with percent concentrations of 50, 25, 12.5, 6.25, 3.13, 1.56, 0.78, and 0.39%. Phytochemical analysis of the ethanol and n-hexane extracts showed the presence of alkaloids and triterpenoids, while chloroform extracts revealed the presence of triterpenoid only. The antioxidant activity test of ethanol extract, chloroform, and n-hexane yielded IC50 values of 99.33 ppm (active), 119.3 ppm (medium), and 192.1 ppm (medium) and the inhibitory zones of C. albicans were 5.17 ± 1.37, 1.78 ± 1.09, and 3.43 ± 1.40 mm, respectively. MIC values of all extracts studied were obtained at 0.78% concentration and MFC values at 1.56%. The rhizome of C. mangga extracts contain flavonoid, alkaloid, and triterpenoid that have antioxidant properties and antifungal activities against C. albicans. Ethanol is the most promising solvent for extracting the active compound of C. mangga rhizome as an antioxidant and antifungal.